Zad 9
a;)2x-7-(3-2x-2(1-2x))=x-11
b;)10-(2(1-x)-3(2x+5))=2(x+5)+1
c;)8-3x-2(4-(x+5))=3(x+1)-1
d;)1-2x-3(2x-(-5+x))=x+4


zad 10
ułamki
a;)x/3-5/6=1/12-x/2
b;)x/2-3/4=7/8+x/4
c;)7/9+x/2=3/2-x/18
d;)x/9+1/2=5/4-x/6+1/12

z rozwiązaniem i sprawdzeniem

1

Odpowiedzi

2010-03-18T19:24:25+01:00
Zad 9
a;)2x-7-(3-2x-2(1-2x))=x-11
2x-7-3+2x+2-4x=x-11
2x+2x-4x-x=-11+7+3-2
-x=-3
x=3

b;)10-(2(1-x)-3(2x+5))=2(x+5)+1
10-2+2x-6x-15=2x+10+1
2x-6x-2x=10+1-10+2+15
-6x=18 /:(-6)
x=-3

c;)8-3x-2(4-(x+5))=3(x+1)-1
8-3x-8+2x+10=3x+3-1
-3x+2x-3x=3-1-8+8-10
-4x=-8 /:(-4)
x=2

d;)1-2x-3(2x-(-5+x))=x+4
1-2x-6x-15+3x=x+4
-2x-6x+3x-x=4-1+15
-6x=18 /:(-6)
x=-3


zad 10
ułamki
a;)x/3-5/6=1/12-x/2
(4x)/12-10/12=1/12-(6x)/12 /*12
4x-10=1-6x
4x+6x=1+10
10x=11/:10
x=11/10
x=1 1/10=1,1

b;)x/2-3/4=7/8+x/4
4x/8-6/8=7/8+2x/8 /*8
4x-6=7+2x
4x-2x=7+6
2x=13 /:2
x=13/2
x=6 ½=6,5

c;)7/9+x/2=3/2-x/18
14/18+9x/18=27/18-x/18 /*18
14+9x=27-x
9x+x=27-14
10x=13 /:10
x=13/10=1 3/10=1,3

d;)x/9+1/2=5/4-x/6+1/12
4x/36+18/36=45/36-6x/36+3/36 /*36
4x+18=45+6x+3
4x-6x=45+3-18
-2x=30 /:(-2)
x=-15


1 5 1